Investigation of the LDPE dust flame propagation effected by the ethylene concentration - Quek, V.; Siti Zubaidah, Sulaiman; Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad (Elsevier Ltd, 2022)
The presence of ethylene (C2H4) gas in a low-density polyethylene (LDPE) combustion process increases the severity of the dust explosion. Understanding dust explosion propagation as influenced by C2H4 concentration is important to characterise the severity of the LDPE dust explosion. Therefore, this paper aims to study the explosion propagation mechanism as influenced by ethylene concentration in LDPE combustion using computational fluid dynamic (CFD) ANSYS FLUENT simulation. Results showed that ethylene concentration influenced the LDPE/C2H4 flame propagation mechanism by increasing the equivalence ratio (ER) to 1.2. The severity of LDPE/C2H4 explosion was also recorded at C2H4 concentration, at ER = 1.2 with explosion pressure = 5.5 bar respectively.